Evaluation of the effectiveness of contrast-enhanced ultrasound in the diagnosis of early hepatocellular carcinoma: a systematic review - AlTaweel, Abdulaziz; Joueidi, Faisal; Joueidi, Ahmad; AlDhubaiki, Ahmed; Qabha, Hamad Mohammed; AlZaid, Homoud Abdulaziz (Frontiers in Radiology, 2025)
ObjectivesTo investigate the evaluation of the effectiveness of contrast-enhanced ultrasound (CEUS) in the diagnosis of small hepatocellular carcinoma (HCC).MethodsA thorough search was conducted for pertinent literature using PubMed, SCOPUS, Web of Science, Science Direct, and Wiley Library. Rayyan QRCI was used throughout this extensive procedure.ResultsOur results included thirteen studies with a total of 2016 patients, and 1672 (82.9%) were males. The follow-up duration ranged from 3 months to 24 months. CEUS was useful in anticipating the early recurrence of HCC, predicting the early recurrence of solitary lesion HCC patients, and differentiating between HCC and intrahepatic cholangiocarcinoma <3 Cm, distinguishing HCC from dysplastic nodules from tiny liver nodules, CEUS in cirrhotic patients. When paired with CEUS, conventional ultrasonography can detect minor HCC and assist in patient monitoring for those who receive an early diagnosis of HCC. CEUS showed high concordance with CECT for diagnosing lesions 2.1–3.0 cm in size. Notable limitations included heterogeneity in protocols and predominance of Asian populations (12/13 studies).ConclusionCEUS offers significant clinical value as a noninvasive diagnostic tool, particularly for 1–3 cm lesions in cirrhotic patients and cases where CT is contraindicated, though protocol standardization and Western population validation remain needed.